A New Catheter Technology to Deliver Vascular Stem-Cells - Brian D Plourde; John R Stark; John P Abraham (Studies on Stem Cells Research and Therapy - Peertechz Publications, 2016)
A new device has been designed, developed and tested to improve the capacity of vascular drug and stem cell delivery. The device consists of a catheter with a multitude of small lumens (instead of a large  central channel lumen). The use of multiple lumens provides a number of benefi ts to medical  intervention. First, the multiple lumens are spread across the catheter cross section. As a consequence,  the medication/stem cells are more effectively dispersed into the artery. Second, the construction of the new catheter has an increased mechanical strength compared to the standard single-lumen catheter - therefore, it is able to resist compressive forces caused by a pressurized balloon. This fact makes the new  design able to preserve medication/stem cell flowrates without causing mechanical hemolysis to the cells. Finally, the newly designed device prohibits clumping of stem cells carried in solution.